Growth and electrochemical properties of CuO nanowires-ZnO microrods composite - Nanda Shakti; Tapendu Mandal; Nayan Mani Das; Dhrubojyoti Roy; Shyam Sunder; Sandeep Kumar; Rahul Pal (Hybrid Advances, 2024)
We have presented simple two step process to synthesize CuO nanowires - ZnO microrods composite using thermal oxidation and hydrothermal method respectively. The synthesized composite showed monoclinic CuO and hexagonal ZnO. Field emission scanning electron microscopy of the samples showed the randomly oriented CuO nanowires have average diameter ∼200 nm and length ∼10 μm. The ZnO microrods have diameter ∼1 μm and length ∼4 μm. The Raman spectrum of sample of CuO nanowires showed the peaks for Raman active (Ag + 2Bg) modes, while that of composite showed E1 and E2 modes of ZnO indicating lattice disorder and oxygen vacancy, along with Bg mode of CuO. Cyclic voltammetry in 0.1 M NaoH electrolyte of the samples showed pseudocapacitance nature of the material. At scan rate of 10 mV/s the CuO–ZnO composite showed specific capacitance of 57 F/g, while CuO nanowires showed ∼5 mF/g at 5 mV/s scan rate.